Assessing the impacts of land use and climate interactions on beekeeping livelihoods in the Taita Hills, Kenya. Issue 4 (19th May 2021) - Newman, Rebecca Jo Stormes; Marchant, Rob; Enns, Charis; Capitani, Claudia
ABSTRACT: Beekeeping is commonly adopted as an additional livelihood activity that can help smallholder farmers diversify and enhance their livelihoods. However, it is unclear whether it is resilient to environmental shocks and stresses. This article investigates beekeepers' experiences and perceptions about challenges to beekeeping in the Taita Hills Mountains, Kenya. Key findings demonstrated that beekeeping has the capacity to substantially increase household income, but there are several challenges which affect beekeeping's sustainability considering predictions around climate and land use change. Bee population decline due to pesticide use was seen as a major challenge across the altitudinal range. In the highland areas deforestation, land use conflicts and cold weather were key issues; whereas in the lowlands water availability and the associated impacts on floral availability were the primary concerns of beekeepers.